Should we write about history, or about doing history? - Jacob Orrje (Lychnos, 2023)
This article explores diverging ways of accounting for methodological questions in the history writing digital history on one hand, and Swedish history of ideas (idéhistoria) on the other. By highlighting differences in how the two fields treat these central historiographical issues, I aim better to understand some of the difficulties of conducting and publishing research in the history of ideas, based on digital-history methods.